Pelatihan Pembuatan Kerajinan Ecoprint Sebagai Pengembangan Kreativitas Anak Di Sekolah Dasar Negeri Wonomerto 1 (Satu) - Dhian Satria Yudha Kartika; Fidda Rahmawati; Viona Eka Rahmawati; Agus Tri Sapta Yudha; Alfin Nur Faizah; Ruldy Rizqi Suhendri (Jurnal Informasi Pengabdian Masyarakat, 2023)
The development of creativity in children is an important aspect in the current era, and one way to develop it is by providing training on ecoprint. Ecoprint is a fabric coloring technique that involves direct contact with printing. The term ecoprint consists of the wordeco," which refers to nature, and "print," which refers to the printing process. In making ecoprint, it uses a simple and easy process that does not need to use machines and is environmentally friendly. The ecoprint coloring technique involves using natural materials such as leaves, flowers, and bark, which contain natural dyes. These materials are used as a substitute for stamps or prints, such as traditional written batik, which can be done with various techniques (pounding, steaming, and fermentation). The method of implementing this activity uses the methods of preparation, outreach, training, and evaluation. The purpose of making ecoprint crafts is to increase children's creativity and skills. The results of this activity are expected to be a provision for elementary school students and have an impact on the surrounding environment in the form of plants being turned into products that have economic value.